Activated carbon from sugarcane bagasse ash for melanoidins recovery. (15th September 2017) - Kaushik, A.; Basu, S.; Singh, K.; Batra, V.S.; Balakrishnan, M.
Abstract: This work investigates the value added utilization of two sugar-distillery wastes: (i) melanoidins, which are complex Maillard reaction products in molasses distillery wastewater, and (ii) unburnt carbon in sugarcane bagasse ash. Activated unburnt carbon (AUC), prepared by deashing and steam activation, had properties comparable to commercial activated carbon (CAC). Both carbons are suitable for melanoidins adsorption followed by desorption using 25% pyridine solution. For AUC, the equilibrium adsorption data is well described by Langmuir isotherm up to 35 °C while Freundlich model fits better at higher temperature. Adsorption using CAC followed Freundlich isotherm at all temperatures. Both carbons followed pseudo second order kinetics and displayed endothermic physisorption. Recovery of melanoidins from AUC (78%) was close to that observed with CAC (80%). Highlights: An activated carbon from sugarcane bagasse ash is prepared. The properties of commercial and prepared activated carbons are comparable. Melanoidins are recovered from activated carbon by adsorption-desorption. Pyridine solution is most effective for desorption of melanoidins. 80% of melanoidins are recovered with commercial and prepared activated carbons.